Solvent extraction of base oil from used lubricant oil : a study on the performance of activated carbon adsorption - 293287 Rosli Mohd. Yunus; Lim, Lee Ping; Adnan Ripin; SOMCHE 2000 (2000 : Putra Jaya, Selangor) (Skudai : Universiti Teknologi Malaysia, 2000)
50